Laparoscopic Cholecystectomy for Left-sided Gallbladder (Sinistroposition) - Reddy, Prasanna Kumar (Society of Laparoendoscopic Surgeons, 2005)
Transposition of the gallbladder to the left side without situs inversus viscerum is rare. These gallbladders are situated under the left lobe of the liver between Segment III and IV or on Segment III to the left of the falciform ligament. Because routine preoperative studies may not detect the anomaly, it may provide the surgeons with an unusual surprise during laparoscopy. Awareness of the unpredictable confluence of the cystic duct into the common bile duct and selective use of intraoperative cholangiography aid in the safe laparoscopic management of this unusual problem.